If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1.4) = 36 Reorder the terms: (-1.4 + x) = 36 Remove parenthesis around (-1.4 + x) -1.4 + x = 36 Solving -1.4 + x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.4' to each side of the equation. -1.4 + 1.4 + x = 36 + 1.4 Combine like terms: -1.4 + 1.4 = 0.0 0.0 + x = 36 + 1.4 x = 36 + 1.4 Combine like terms: 36 + 1.4 = 37.4 x = 37.4 Simplifying x = 37.4
| 36(x-1.4)= | | 20m^2+43m+14= | | 11-45=5(x-3)-4 | | 17(5c-1)-14=83c+17 | | -19n+12=-15n-12 | | 42=-7y | | 11=u-7 | | 2.5h=80 | | 11-12b=3 | | 4u+8=5u+3 | | 2.5=80 | | 4x=3x-7 | | 3y-y=4-18 | | 5t^2-8t=3 | | -3=7y | | -3v=-18 | | 5-8x=55-22x | | 6=v+15 | | -9+14=-2u+7u | | -0.625+m=0.333334 | | -6v-6v=-7-18 | | 7v-1=6v-6 | | 4x+33=14x-77 | | 30X-6=4 | | 5x^3-2=x-x^2 | | 4+3=-2w-3w | | x^2+4x+10=3 | | 7(2x-4)=2x+8 | | 5x+3=4x+4 | | -4+3y=3+1 | | 2x-13=109 | | 4+2=w+7w |